2010
DOI: 10.1103/physreva.81.043404
|View full text |Cite
|
Sign up to set email alerts
|

Low-momentum-transfer nonrelativistic limit of the relativistic impulse approximation expression for Compton-scattering doubly differential cross sections and characterization of their relativistic contributions

Abstract: The nonrelativistic (nr) impulse approximation (NRIA) expression for Compton-scattering doubly differential cross sections (DDCS) for inelastic photon scattering is recovered from the corresponding relativistic expression (RIA) of Ribberfors [Phys. Rev. B 12, 2067(1975] in the limit of low momentum transfer (q → 0), valid even at relativistic incident photon energies ω 1 > m provided that the average initial momentum of the ejected electron p i is not too high, that is, p i < m. This corresponds to a binding e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…where E(p z ) = m 2 c 4 + p 2 z c 2 and q is the modulus of the momentum transfer vector q ≡ k i − k f . Furthermore, previous study revealed that p z and E(p z ) are exactly the energy and momentum minimum of the initial state electrons activated in Compton scattering [27], namely…”
Section: A Former Treatmentsmentioning
confidence: 95%
See 1 more Smart Citation
“…where E(p z ) = m 2 c 4 + p 2 z c 2 and q is the modulus of the momentum transfer vector q ≡ k i − k f . Furthermore, previous study revealed that p z and E(p z ) are exactly the energy and momentum minimum of the initial state electrons activated in Compton scattering [27], namely…”
Section: A Former Treatmentsmentioning
confidence: 95%
“…Recently, LaJohn compared various treatments of RIA formulation in a similar manner, and achieved the nonrelativistic limit of RIA for low-momentum-transfer cases [27]. However, his work is limited to hydrogen-like systems.…”
Section: Introductionmentioning
confidence: 99%
“…NR expressions for DDCS can provide fairly accurate predictions for the DDCS of light atoms (see [18,19]) if the incident photon energy is ω i = m or θ → 0° [20]; otherwise, relativistic factors must be included ([6, 7, 21-24] for examples). If there is a need to obtain a CP from DDCS in a relativistic regime, the most straightforward approach for Compton scattering is RKJ approximation, which is fairly accurate overall ω i values; if the binding energy (E b ) is low, it becomes less accurate with increasing E b .…”
Section: Introductionmentioning
confidence: 99%
“…Alternative models to Ribberfors' DDCS have been developed and even expanded to the Triply Differential Compton scattering Cross-Section (TDCS), including the dependence of the ejection direction of the Compton electron [16][17][18][19][20][21]. These models have primarily explored the numerical calculation of K-shell Compton scattering cross-sections for numerous materials over an energy range of a few keV [16,17,20] to 1 MeV [20].…”
Section: Introductionmentioning
confidence: 99%
“…These models have primarily explored the numerical calculation of K-shell Compton scattering cross-sections for numerous materials over an energy range of a few keV [16,17,20] to 1 MeV [20]. Of the wide range of different approaches in both the RIA and Independent Particle Approximation (IPA), one of the most promising is that described in the seminal paper from Kaliman et al [17].…”
Section: Introductionmentioning
confidence: 99%